In my defence or yours: Children's guilt subtypes and bystander roles in bullying. Issue 6 (1st November 2020) - Nocentini, Annalaura; Colasante, Tyler; Malti, Tina; Menesini, Ersilia
ABSTRACT: This study aimed to understand if specific types of guilt were associated with distinct bystander roles. Specifically, we tested if differences in children's endorsement of ethical vs. sanction-oriented guilt predicted differences in defending and outsider behaviours. Participants were 574 primary Italian school students from 4th and 5th grade. Measures included self-reported guilt feelings and peer reports of defender and outsider behaviours. Results showed that defenders and outsiders were characterized by different types of guilt. Ethical guilt and a marked lack of happy victimizing (i.e., feeling happy after transgressing) characterized defenders, whereas the link between outsider behaviours and ethical guilt was weaker. Also, outsider males tended to endorse externally dependent feelings of sanction-oriented guilt. Overall, defenders appear to feel and act in others' defence, whereas the emotions and behaviours of outsiders may be more focused on their own defence.